Exposure to latest technology in industry, UMP alumni preferred by employers - Siti Nurfarmy, Ibrahim (2021)
PEKAN, 12 July 2021 - Students must always be flexible and ready to learn something new, especially facing the new norms of the Covid-19 pandemic.